Writing was everything - Kazin, Alfred 1915-1998 (Harvard Univ. Press, 1995)
A deft blend of autobiography, history, and criticism that moves from New York in the 1930s to wartime England to the postwar South, Writing Was Everything emerges as a reaffirmation of literature in an age of deconstruction and critical dogma. In his encounters with books, Kazin shows us how great writing matters and how it involves us morally, socially, and personally on the deepest level. Whether reflecting on modernism, southern fiction, or black, Jewish, and New Yorker writing, or sharing anecdotes about Richard Wright, Saul Bellow, and John Cheever, he gives a penetrating, moving account of literature observed and lived. In his life as a critic, Kazin personifies the lesson that living and writing are necessarily intimate.
Keywords: Kazin, Alfred <1915-1998>; Kazin, Alfred -- 1915-1998; Geschichte 1900-2000; Literair leven; Geschichte; American literature -- History and criticism -- Theory, etc; Criticism -- United States -- History -- 20th century; Critics -- United States -- Biography; Autobiografie; USA; United States -- Intellectual life -- 20th century; Biografie